Representative taxa in field trials for environmental risk assessment of genetically modified maize. Issue 6 (30th August 2013) - Albajes, R.; Lumbierres, B.; Pons, X.; Comas, J.
Abstract: When assessing the benefits and risks of transgenic crops, one consideration is their relative effects on non-target arthropod (NTA) abundance and functions within agroecosystems. Several laboratory and field trials have been conducted in Spain since the late 1990s to assess this issue. A consideration in the design of field trials is whether it is necessary to sample most NTAs living in the crop or only representative taxa that perform main ecological functions and have a good capacity to detect small changes in their abundance. Small changes in the field abundance of an effective representative taxon should be detectable using standard experimental protocols. The ability of a species to reveal differences across treatments may be analysed by examining the detectable treatment effects for surveyed non-target organisms. Analysis of data from several NTAs recorded in 14 field trials conducted over 10 years using complete block designs allowed us to select a number of representative taxa capable of detecting changes in the density or activity of arthropod herbivores, predators, parasitoids and decomposers in transgenic and non-transgenic maize varieties. The most suitable NTA as representative taxa (with detectable treatment effects below 50%) included leafhoppers among arthropod herbivores, Orius spp., Araneae, and Carabidae among predators, chalcidids, particularly the family Mymaridae, among parasitoids and Chloropidae as decomposer. Details of sampling techniques for each sampled taxa and their advantages and disadvantages are discussed. It is concluded that abundance of taxa is the most influential factor determining their capacity to detect changes caused by genetically modified varieties.